Brand Image and Quality Drive Purchases in Indonesia: Citra Merek dan Kualitas Mendorong Pembelian di Indonesia - Muhammad Zulkufli; Sumartik (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores how brand image, sales promotion, and product quality influence customer purchase intentions at PT. BERKAH SUKSES PERSADA, a fast-food catering company in Sidoarjo. Using a sample of 100 customers determined by the Slovin formula, data were collected through questionnaires and analyzed with multiple linear regression using SPSS. The results show that brand image and product quality have a highly positive and significant impact on purchase intentions, while sales promotions have a positive but lesser effect. The findings suggest that enhancing these factors can significantly boost customer purchase intentions, offering valuable insights for marketing strategies in the competitive fast-food industry. Highlight: Brand Impact: Strong brand image significantly boosts customer purchase intentions. Quality Matters: High product quality directly influences positive buying decisions. Promotion Effect: Sales promotions enhance purchase intentions to a lesser extent. Keyword: Brand Image, Sales Promotion, Product Quality, Customer Purchase Intentions, Fast-Food Industry